Effect of Time Interval and Frequency of Hospitalization Because of Fluid Overload on Survival in Peritoneal Dialysis: Thailand Experience - Jaruwan Thuanman; Pornpen Sangthawan; Kavin Thinkhamrop; Bandit Thinkhamrop; Jadsada Thinkhamrop; Siribha Changsirikulchai (Kidney360)
Key Points. High mortality was found in patients on peritoneal dialysis who were hospitalized early or frequently because of fluid overload. Interval time and frequency of hospitalization because of fluid overload are clinical indicators for the need of intensive fluid management. Background. Fluid overload (FO) is common and linked to high mortality in patients undergoing peritoneal dialysis (PD). This study evaluates the effect of time interval and frequency of FO-related hospitalizations on mortality and patient survival rates in patients on PD. Methods. Data from patients on PD voluntarily registered in the Database of Peritoneal Dialysis in EXcel were reviewed. We included patients who started PD between January 2008 and December 2018, had a history of FO-related hospitalizations after starting PD, and were followed until December 2020 or death. We analyzed the time interval to the first FO-related hospitalization after starting PD, number of such hospitalizations, and cumulative FO-free time. Mortality and patient survival rates were calculated, and multiple Cox regression identified factors associated with mortality. Results. Among 1858 patients hospitalized because of FO, those hospitalized within 12 months of starting PD or with <12 months of cumulative FO-free time had high mortality rates of 38.8 and 40.3 per 100 patient-years, respectively. One-year survival rates were 70.1% for those with a time to first FO-related hospitalization within 12 months of starting PD and 68.7% for those with <12 months of cumulative FO-free time. Adjusted hazard ratios were 2.92 (2.31–3.69) for a cumulative FO-free time of <12 months, 1.53 (1.18–1.99) for time to first FO-related hospitalization within 12 months and 1.05 (1.03–1.07) per FO-related hospitalization. Conclusions. The time interval to the development of FO significantly affects mortality in patients undergoing PD. Podcast. This article contains a podcast at https://dts.podtrac.com/redirect.mp3/www.asn-online.org/media/podcast/K360/2024_11_21_KID0000000576.mp3